Novel Anticancer Triple Formula Based on Aptamer-Conjugated PEGylated Nanoliposomes - Ali Al-Samydai PhD; Hamdi Nsairat PhD; Moath Alqaraleh PhD; Maha N. Abu Hajleh PhD; Areej Jaber PhD; Lidia Al-Halaseh PhD; Hanan Azzam MS; Qasim Khalid Alazzawi PhD; Israa Al-Ani PhD; Simone Carradori PhD; Walhan Alshaer PhD (Technology in Cancer Research & Treatment, 2025)
Background Cancer remains a leading cause of death worldwide, necessitating the development of affordable and innovative therapies to reduce its human and economic burden. Objectives In this study, we aimed to develop a synergistic anticancer formula encapsulated in nanoliposomes to enhance efficacy and minimize side effects. Additionally, we explored the effect of aptamer conjugation on the efficacy and stability of the formula. Methods The Etoricoxib-β-cyclodextrin complex was prepared using the kneading method, and nanoliposomes were developed via thin film hydration. The AS1411 aptamer was conjugated to the nanoliposomes to target nucleolin, a protein overexpressed in cancer cells. The etoricoxib-β-cyclodextrin complex was characterized using proton nuclear magnetic resonance, and various liposome properties, including size, encapsulation efficiency, and stability, were optimized. The release profiles of the active compounds were evaluated using high-performance liquid chromatography, and their cytotoxicity was assessed in human cancer cell lines. Results The nanoliposomes co-loaded with the three agents and their aptamer-conjugated counterpart showed optimal characteristics, with particle sizes of 133.3 ± 1.45 nm and 174.8 ± 4.78 nm, and zeta potentials of −15.26 ± 1.80 mV and −15.66 ± 2.57 mV, respectively. The encapsulation efficiencies were 88.63% (raloxifene), 41.73% (etoricoxib), and 39.26% (naringin) without the aptamer, and 81.99%, 36.66%, and 38.33%, respectively, with the aptamer. The IC 50 of the formula for the three co-loaded agents was 167.4 µg/mL for A549 cells and 2.6 µg/mL for MCF-7 cells. Cytotoxicity was further enhanced using their aptamer conjugate, particularly against the MDA-MB-231 cell line. Conclusion The novel triple-drug-loaded, aptamer-conjugated nanoliposome formula may be a future cancer treatment strategy.